Longitudinal Associations Between Sleep Disturbance Trajectories and Internet Gaming Disorder Mediated by Self-Control: A Six-Wave Longitudinal Investigation - Liu H; Qiao X; Shi X (Psychology Research and Behavior Management)
Hongping Liu,* Xiaofei Qiao,* Xuliang Shi College of Education, Hebei University, Baoding, Hebei Province, 071002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuliang Shi, Associate Professor at the College of Education, Hebei University, Baoding, 071002, People’s Republic of China, Email shixl163@163.comObjective: The present study aims to analyze the heterogeneous trajectories of sleep disturbance (SD) among college students and to examine whether self-control mediates the association between sleep disturbance trajectories and Internet gaming disorder (IGD).Methods: A total of 4352 students were initially invited to participate, and 4191 (Mage = 19.12, SD = 0.98; 46.9% females) students were included as valid respondents at the first time-point. This study spanned six waves (from 2019 to 2022) with a six-month interval between each wave. Sleep disturbance was measured from Time 1 to Time 4, self-control was measured at Time 5, and Internet gaming disorder was measured at Time 6. Growth mixture modeling (GMM) was applied to identify latent classes of sleep disturbance over the four waves. Mediation analysis was conducted to examine the mediating role of self-control between sleep disturbance trajectories and IGD.Results: The results of growth mixture modelling yielded a four-class solution for sleep disturbance: a stable-low group, an increasing group, a decreasing group, and a stable-high group. Additionally, the results of mediation models showed that increased sleep disturbance is associated with a higher likelihood of individuals becoming more addicted to Internet games due to decreased self-control. Conversely, improved sleep quality may decrease the likelihood of engaging in Internet games via by promoting higher levels of self-control.Conclusion: Future prevention and intervention programs targeted at improving self-control may decrease the possibility of developing IGD.Keywords: Internet gaming disorder, sleep disturbance trajectories, self-control, college students, longitudinal cohort